Odpowiedź:
[tex]a)\\\\\frac{1}{3}(x+4)=2x-2\\\\\frac{1}{3}x+\frac{4}{3}=2x-2\ \ /\cdot3\\\\x+4=6x-6\\\\x-6x=-6-4\\\\-5x=-10\ \ /:(-5)\\\\x=2\\\\\\b)\\\\\frac{1}{5}(x+3)=-x+5\\\\\frac{1}{5}x+\frac{3}{5}=-x+5\ \ /\cdot5\\\\x+3=-5x+25\\\\x+5x=25-3\\\\6x=22\ \ /:6\\\\x=\frac{22}{6}\\\\x=\frac{11}{3}\\\\x=3\frac{2}{3}[/tex]
[tex]c)\\\\\frac{2}{3}(x-2)=4x+1\\\\\frac{2}{3}x-\frac{4}{3}=4x+1\ \ /\cdot3\\\\2x-4=12x+3\\\\2x-12x=3+4\\\\-10x=7\ \ /:(-10)\\\\x=-\frac{7}{10}\\\\\\d)\\\\5(x-3)=6(x+2)\\\\5x-15=6x+12\\\\5x-6x=12+15\\\\-x=27\ \ /\cdot(-1)\\\\x=-27\\\\\\e)\\\\\frac{x+2}{5}+1=5\ \ /\cdot5\\\\x+2+5=25\\\\x+7=25\\\\x=25-7\\\\x=18[/tex]